The Effect of Parenting Style on Adolescent Resilience: An Empirical Analysis based on CEPS(2014-2015) Data - Du, Huan; Zou, Shuling (International Journal of Social Sciences and Public Administration, 2024)
It is the key to help adolescents with low stress level to establish good mental health ability and improve their unreasonable parenting style, which is to realize psychosocial integration and improve physical and mental health of vulnerable groups. Using the survey data of China Education Tracking Survey (CEPS) for the 2014-2015 academic year, a valid sample size of 5609 were selected and selected, and multiple linear regression method was used to study the impact of parental parenting styles on the resilience level of adolescents. The findings are as follows: (1) The current parenting style of Chinese adolescents is mainly authoritative, and the level of resilience of adolescents under each parenting type is in the order of authoritative > permissive > authoritarian > neglective; (2) In terms of the influence on the level of resilience of adolescents, the four types of upbringing have a significant positive correlation; (3) Regression results showed that individual characteristics, peer support and family environment factors had a certain impact on adolescent resilience, but the difference of parenting style had a more obvious impact on adolescent resilience. In order to bring into play the key role of parenting style on the level of resilience of adolescents, social workers should focus on the change of parenting concept of unreasonable parenting type; From the perspective of advantage, to improve the self-efficacy of adolescents under unreasonable parenting types, to create a good family environment and clear self-cognition for adolescents to improve their resilience level.